Image steganography using web application / Nor Arzami Othman ... [et al.] - Othman, Nor Arzami; Shariffudin, Muhammad Nur Harith; Osman, Mohd Nizam; Sedek, Khairul Anwar (UiTM Cawangan Perlis, 2023)
Nowadays most people are workaholics, driven by intense peer pressure to break new ground. Therefore, rather than using books as their source material, photographic memories are kept as images. However, to protect sensitive information, reliable and secure communication techniques are necessary in many real world situations. This research offers a user-friendly interface for securely embedding and extracting secret information within digital images. The primary goals are to design a steganographic algorithm for concealing data in images and to evaluate the usability of image steganography while keeping the quality of images and the access to decode the image. The application utilizes an advanced steganographic algorithm, which is Randomized Least Significant Bit (RLSB), to ensure robust data concealment while maintaining the visual integrity of the cover image. Users can upload their desired image, select the preferred steganographic algorithm, and encode the hidden data for added security. The web application supports encoding and decoding images for concealing data in images. To evaluate its performance, extensive testing was conducted, including embedding and extracting data using different image formats. The results demonstrated the application's effectiveness in hiding information while preserving image quality. The web application proved to be a versatile and practical tool with applications in various fields such as cryptography and digital forensics. In conclusion, the Image Steganography Web Application provides a convenient and secure solution for individuals and organizations needing to transmit sensitive data covertly within images, ensuring data privacy and integrity in an intuitive and user-friendly manner.